ABOUT ENHANCING EDUCATIONAL ACTIVITIES IN INFORMATICS - Tusunboyev, Olmos; Zokirov, Mamajon; Saydayev, Obid (Физико-технологического образование, 2022)
The innovative pedagogical technologies as a modern teaching methods and tools in educational system is studied. The innovative pedagogical technologies not only create the basis for the competitiveness of any institution in the market of educational services, but allow the intensive development of teacher and student personality, democratization of teacher-student interaction and communication, humanization of the educational process, orientation of students to active learning and self-formation, professionalism of teachers and so on